(untitled) (Research, Society and Development, 2022)
Objective: This work aimed of to review the implications of anti-TNF-α therapy in COVID-19 patients associated with the genetic polymorphism (TNF-α polymorphisms in the region-308) of this pertinent cytokine Methodology: Electronic searches were carried out on PUBMED Central, BVS/BIREME, Web of Science and The Cochrane Library with the aid of key-words. Results: Twenty-six articles were collected. Anti-TNF-α therapy was interpreted and evaluated. Conclusions: Although scarce information is available in the current literature, anti- TNF-α therapy seems to be a viable clinical approach for hospitalized COVID-19 patients who do not need oxygen supply. The genetic polymorphisms, although relevant, may be useful for further researched to assess the clinical response in different research groups.